Technoeconomic analysis of hydrogen versus natural gas considering safety hazards and energy efficiency indicators - Osama Massarweh; Yusuf Bicer; Ahmad Abushaikha (Scientific Reports)
Abstract Hydrogen ( $$H_2$$ ) is emerging as a key alternative to fossil fuels in the global energy transition. This study presents a comparative techno-economic analysis of $$H_2$$ and natural gas (NG), focusing on safety hazards, energy output, $$CO_2$$ emissions, and cost-effectiveness aspects. Our analysis showed that, compared to NG and other highly flammable gases like acetylene ( $$C_2\,H_2$$ ) and propane ( $$C_3\,H_8$$ ), $$H_2$$ has a higher hazard potential due to factors such as its wide flammability range, low ignition energy, and high flame speed. In terms of energy output, 1 kg of NG produces 48.60 MJ, while conversion to liquefied natural gas (LNG), grey $$H_2$$ , and blue $$H_2$$ reduces energy output to 45.96 MJ, 35.45 MJ, and 31.21 MJ, respectively. Similarly, while unconverted NG emits 2.72 kg of $$CO_2$$ per kg, emissions increase to 3.12 kg for LNG and 3.32 kg for grey $$H_2$$ . However, blue $$H_2$$ significantly reduces $$CO_2$$ emissions to 1.05 kg per kg due to carbon capture and storage. From an economic perspective, producing 1 kg of NG yields a profit of $0.011. Converting NG to grey $$H_2$$ is most profitable, yielding a net profit of $0.609 per kg of NG, while blue $$H_2$$ , despite higher production costs, remains viable with a profit of $0.390 per kg of NG. LNG conversion also shows profitability with $0.061 per kg of NG. This analysis highlights the trade-offs between energy efficiency, environmental impact, and economic viability, providing valuable insights for stakeholders formulating hydrogen and LNG implementation strategies.